Analisis Penggunaan Majas pada Puisi “Diponegoro” Karya Chairil Anwar - Hura, Dernius; Ndraha, Laurensia (Indo-MathEdu Intellectuals Journal, 2024)
Purpose of this research is to find out and analyze what figures of speech are used in the poem entitled "Diponegoro" by Chairil Anwar. This type of research is qualitative research. The method used is descriptive qualitative method. The data source used in this study is a poem entitled "Diponegoro" by Chairil Anwar. Data analysis techniques are carried out using interactive techniques which include three things, namely data reduction, data presentation, and drawing conclusions. The results showed that the figure of speech used in the poem entitled "Diponegoro" by Chairil Anwar is a figure of speech of personification, hyperbole, metaphor, synecdoche totem pro parte, metonymy, oxymoron, and sarcasm